SNOW TROUT, Schizothorax richardsonii (GRAY), FROM THE RIVER YAMUNA, UTTARAKHAND, INDIA: A STUDY ON THE LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION FACTOR - RAYAL, RAJESH; SAHER, ALVEENA; MADAN, SANJAY; BHARTI, SHRADDHA; RANA, NIDHI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The length-weight relationship and relative condition factor of snow trout, Schizothorax richardsonii (Gray), from the Yamuna River in Uttarakhand are investigated in this study. The results of this study revealed that there is a close relationship between length and weight. For sex-specific data, the regression coefficient ranged from 2.621 for males (r = 0.7683) to 2.795 for females (r = 0.8027) The relative condition factor was maximum 0.645 ± 0.061 for males and 0.756 ± 0.086 for females during the winter season. The minimum value was calculated as 0.019±0.002 for males and 0.048±0.007 for females in the monsoon season. The relative condition factor indicated that the winter season represented better feeding opportunities and suitability of the river habitat.